Automated testbed development for tree radar - Ang Eng Hwee (Nanyang Technological University, 2023)
This report is mainly focused on designing a slider system for the automation and monitoring of the health of tree trunks. Tree health assessment is very important in Singapore, especially in light of the increasing number of incidents of tree failures. Despite the efforts by the National Parks Board (NParks) to prevent such incidents, there are gaps in their preventive methods. Researchers at NTU have been using Ground Penetrating Radar (GPR) methods to obtain data and study the condition of trees. However, the current process of data collection is labor-intensive and time-consuming. The objective of this project is to develop an automated testbed system that can obtain measurement data of a tree's health. This will be achieved by developing a testbed for the tree radar with functionalities such as a motorized slider and rotator, controlled by Arduino and Python code, to automate the process of obtaining measurement data. The implementation of this automated system will allow researchers and arborists to capture data from trees with minimal labor, time, and supervision.